Analysis of the potential of building ramps in hydrotechnical structures as a means of facilitating fish migration - Tomasz Tymiński; Justyna Mumot; Radosław Strojny; Dorota Karpowicz (Acta Scientiarum Polonorum. Formatio Circumiectus)
Measures aimed at preserving “ecological corridors” in rivers are a difficult and complex issue that requires specialized knowledge from many science disciplines. Fishways are one of the most important solutions that ensure the ecological continuity of rivers for fish, particularly due to their near-natural design. A characteristic feature of their construction is the use of natural building materials (stones, tree stumps, gravel, and vegetation) in such a way that their appearance resembles asmall watercourse. The design of hydraulic fishways is based only on the criterion of maximum speed (vmax) and the parameter of unitary energy of water E; it does not provide complete information about these devices’ efficiency. In order to produce optimal flow conditions for ichthyofauna in the fishway, there is a need for research into the spatial distribution of the hydraulic parameters, such as disorders of the flow velocity field or distributions of turbulence (Tu). The aim and scope of this work was to examine the potential of building fish ramps as a means of creating a watercourse through hydrotechnical structures, in order to facilitate fish migration. For this purpose, research was conducted on a physical model in the water laboratory of Prof. Julian Wołoszyn at the Wrocław University of Environmental and Life Sciences. A physical model of a fish ramp was built. Depths and flow speeds at the established water flow rate were measured. Depths of water in the fishway were evaluated in strategic places for fish – i.e. at the entrance and exit of the fishway and between cylindric stones (flow obstacles) on the ramp. The speed was measured at mesh nodes which are spaced at intervals of 15 cm along the length of the riverbed and of 10 cm across the cross section. Maps of the spatial distribution of the flow velocity were drafted based on the results obtained, from which maximum and minimum speeds, stream/current distribution and a rest zone for fish were analyzed. Based on these results it was decided to carry out an attempt to assess the effectiveness of ramps as a means of enabling fish migration.